2009
DOI: 10.1158/0008-5472.can-08-3726
|View full text |Cite
|
Sign up to set email alerts
|

The CD4+ T-Cell Response of Melanoma Patients to a MAGE-A3 Peptide Vaccine Involves Potential Regulatory T Cells

Abstract: Melanoma patients were injected with various vaccines containing a MAGE-A3 peptide presented by HLA-DP4. Anti-MAGE-A3.DP4 T cells were not detectable in the blood before vaccination, but their frequencies after vaccination ranged from 2 Â 10 À6 to 2 Â 10 À3 among the CD4 + blood T lymphocytes of the patients. The CD4 + blood T lymphocytes that stained ex vivo with HLA-DP4 tetramers folded with the MAGE-A3 peptide were selected by flow cytometry and amplified under clonal conditions. About 5% of the CD4 + T-cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…This is surprising given the low amounts of IL-12p70 released from cocktailmatured DC in vitro but may be explained by their expression of CD70 [20,54]. The vaccine-specific Th cells were FOXP3-negative, indicating that vaccine-specific natural Treg were not induced, which is counterintuitive to a previous report [55], yet compatible with recent Treg cloning data [56]. Vaccine-specific CTL were, however, only weakly detectable ex vivo, but the CTLp frequency was markedly increased, and many CTL were of high affinity.…”
Section: Modc As a Focus For Comparisonsupporting
confidence: 52%
“…This is surprising given the low amounts of IL-12p70 released from cocktailmatured DC in vitro but may be explained by their expression of CD70 [20,54]. The vaccine-specific Th cells were FOXP3-negative, indicating that vaccine-specific natural Treg were not induced, which is counterintuitive to a previous report [55], yet compatible with recent Treg cloning data [56]. Vaccine-specific CTL were, however, only weakly detectable ex vivo, but the CTLp frequency was markedly increased, and many CTL were of high affinity.…”
Section: Modc As a Focus For Comparisonsupporting
confidence: 52%
“…In mice, it has been reported that the expansion of iTregs upon vaccination dampens antitumor Th1 responses [87]. In human, the group of Peter Van der Bruggen has demonstrated that the CD4 + T-cell response of melanoma patients to a MAGE-A3-derived peptide vaccine involves regulatory T cells [88]. In individuals vaccinated with E6/E7-derived long peptides, immunosuppressive cells has been shown to expand [89], correlating to the development of resistance against an anti-HPV therapeutic vaccine [90].…”
Section: Specificity Of Tregsmentioning
confidence: 99%
“…Most recently, the Wilm's TA overexpressed by leukemias was shown to stimulate TA-specific Treg clones generated in vitro from PBLs of normal donors (14). In addition, immunization with one MAGE-A3 peptide resulted in induction of TA-specific regulatory T cells isolated from PBLs of vaccinated melanoma patients (15).…”
mentioning
confidence: 99%